Meckel's diverticulum found in human fetus: An anatomical case report with commentaries on arterial supply and a concise literature review - Andrzej Żytkowski; Edward Clarke; Agata Mazurek; Michał Golberg; Artur Derlatka; Joe Iwanaga; R. Shane Tubbs; Grzegorz Wysiadecki (Elsevier, 2022)
Background: Although Meckel's diverticulum is a well-known variation, there is rarely an opportunity to trace the detailed anatomy of this structure in dissection material with resin-injected arteries, especially in fetuses. This report presents a detailed description of the ileal diverticulum found in a human fetus, including its vascularization and relationship to the mesentery. Case description: A persistent and well-developed Meckel's diverticulum was found during dissection of a female fetus (CRL = 19 cm). The diverticulum was located in the distal portion of the ileum, among the small intestine loops, and occupied the antimesenteric border of the intestine. It had a broad base and narrowed towards the end; its end was free. Since the arteries were injected with red resin, nutrient branches to the diverticulum from the ileal arteries could be traced in detail. Conclusions: Anatomically, diverse variants of Meckel's diverticulum can occur. The diverticulum can have its own mesentery, and its primary blood supply is from the remnant vitelline artery.